An Evidence-Based Approach for Choosing Post-exercise Recovery Techniques to Reduce Markers of Muscle Damage, Soreness, Fatigue, and Inflammation: A Systematic Review With Meta-Analysis - Dupuy, Olivier; Douzi, Wafa; Theurot, Dimitri; Bosquet, Laurent; Dugué, Benoit (Frontiers in Physiology, 2018)
Introduction: The aim of the present work was to perform a meta-analysis evaluating the impact of recovery techniques on delayed onset muscle soreness (DOMS), perceived fatigue, muscle damage and inflammatory markers after physical exercise. Method: Three databases including PubMed, Embase, and Web-of-Science were searched using the following terms: (“recovery” or “active recovery” or “cooling” or “massage” or “compression garment” or “electrostimulation” or “stretching” or “immersion” or “cryotherapy”) and (“DOMS” or “perceived fatigue” or “CK” or “CRP” or “IL-6”) and (“after exercise” or “postexercise”) for randomized controlled trials, crossover trials, and repeated-measure studies. Overall, 107 studies were included. Results: Active recovery, massage, compression garments, immersion, contrast water therapy and cryotherapy induced a small to large decrease (-2.26 < g < -0.40) in the magnitude of DOMS, while there was no change for the other methods. Massage was found to be the most powerful technique for recovering from DOMS and fatigue. In terms of muscle damage and inflammatory markers, we observed an overall moderate decrease in creatine kinase [SMD (95% CI) = -0.37 (-0.58 to -0.16), I2 = 40.15%] and overall small decreases in interleukin-6 [SMD (95% CI) = -0.36 (-0.60 to -0.12), I2 = 0%] and C-reactive protein [SMD (95% CI) = -0.38 (-0.59 to -0.14), I2 = 39%]. The most powerful techniques for reducing inflammation were massage and cold exposure. Conclusion: Massage seems to be the most effective method for reducing DOMS and perceived fatigue. Perceived fatigue can be effectively managed using compression techniques, such as compression garments, massage or water immersion.